The shift to remote work lessens wage-growth pressures - Barrero, Jose Maria,Bloom, Nicholas,Davis, Steven J.,Meyer, Brent,Mihaylov, Emil (IZA - Institute of Labor Economics, 2022)
The recent shift to remote work raised the amenity value of employment. As compensation adjusts to share the amenity-value gains with employers, wage-growth pressures moderate. We find empirical support for this mechanism in the wage-setting behavior of U.S. employers, and we develop novel survey data to quantify its force. Our data imply a cumulative wage-growth moderation of 2.0 percentage points over two years. This moderation offsets more than half the real-wage catchup effect that Blanchard (2022) highlights in his analysis of near- term inflation pressures. The amenity-values gains associated with the recent rise of remote work also lower labor's share of national income by 1.1 percentage points. In addition, the
10419/263601
Keywords: Graue Literatur; Telearbeit; Lohnbildung; Lohnniveau; Lohnquote; USA; remote work; amenity value; wage growth; inflation dynamics; recession risk; business expectations; labor's share of national income; wage compression